DAMPAK FAKTOR INTERNAL DAN EKSTERNAL TERHADAP PROFITABILITAS PERBANKAN (Studi pada Bank Konvensional di Indonesia Periode Januari 2012 - Januari 2019) - Silvia Hendrayanti; Wachidah Fauziyanti; Eni Puji Estuti (Sekolah Tinggi Ilmu Ekonomi Semarang, 2019)
The bank is one of the financial institutions which has the activity of collecting funds from the public in the form of deposits and channeling them to the public in the form of credit or other forms in order to improve the lives of many people. The purpose of the banking business is to make a profit. Banking profitability is one of the most important indicators in determining the success of a bank and can be used as a basis for banking policies and strategies in the coming period. The purpose of this study was to examine the effect of Operating Costs on Operating Income (BOPO), Capital Adequacy Ratio (CAR), Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), Firm size, and inflation on Return on Assets (ROA). The population in this study is the Conventional Banks in Indonesia in the period January 2012-January 2019. The sample selection using the purposive sampling method with the criteria for the monthly financial statements of all conventional banks in Indonesia during the observation period January 2012-January 2019 has been published by Bank Indonesia. The number of samples used in this study were 85 samples. In this study the research methods used descriptive analysis, Classical Assumptions (Normality, nonautocorrelation, Multicollinearity, Heteroscedasticity), multiple regression model analysis, hypothesis testing (z-statistic test, F-statistic test, and coefficient of determination (R2) test). The results of this study found that Operating Costs to Operating Income (BOPO) had a negative and significant effect on Return On Assets (ROA), Capital Adequacy Ratio (CAR) and Net Interest Margin (NIM) had a negative and significant effect on Return on Assets (ROA) ), Loan to Deposit Ratio (LDR) has a positive but not significant effect on Return On Assets (ROA), Firm size and inflation have a negative and significant regression coefficient on Return On Assets (ROA).